2008
DOI: 10.1590/s0100-29452008000400046
|View full text |Cite
|
Sign up to set email alerts
|

Análise comparativa de nutrientes funcionais em morangos de diferentes cultivares da região de Lavras-MG

Abstract: RESUMO -O morango é um pseudofruto muito apreciado pela população brasileira, e seu cultivo vem sendo implantado na região de Lavras. É um alimento funcional, pois, além das suas propriedades nutricionais, também possui substâncias ativas, que mantêm ou melhoram a saúde do organismo humano. O objetivo deste trabalho foi avaliar alguns compostos do morango que tenham efeitos benéficos para a saúde humana, em diferentes cultivares da região de Lavras-MG. O delineamento utilizado foi o inteiramente casualizado, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 5 publications
(7 reference statements)
2
4
0
11
Order By: Relevance
“…The greatest contents of vitamin C (mg ascorbic acid 100 g −1 ) were found in 'Camarosa' (76.36), 'Campinas' (75.95), 'Festival' (76.69), 'Oso Grande' (79.39), and 'Toyonoka' (83.77). In a study conducted in Lavras-MG with different strawberry cultivars [32], similar values were found for cv. Camarosa and lower values for cv.…”
Section: Variability Due To Harvesting Timessupporting
confidence: 68%
“…The greatest contents of vitamin C (mg ascorbic acid 100 g −1 ) were found in 'Camarosa' (76.36), 'Campinas' (75.95), 'Festival' (76.69), 'Oso Grande' (79.39), and 'Toyonoka' (83.77). In a study conducted in Lavras-MG with different strawberry cultivars [32], similar values were found for cv. Camarosa and lower values for cv.…”
Section: Variability Due To Harvesting Timessupporting
confidence: 68%
“…Rocha, Abreu, Corrêa, Santos & Fonseca (2008), observed concentrations of 8.7, 8.4 e 7.6 g of K kg -1 of DM, respectively. However, in that research they did not used different fertilizer rates and results obtained match to the observed without fertilization, which confirms what we obtained: K fruit concentration increases with application of greater rates of K fertilizer.…”
Section: Discussionmentioning
confidence: 89%
“…No entanto, além de ter uma produção sazonal, o morango é uma fruta muito delicada, com alta taxa respiratória, sendo, por isso, altamente perecível (ROCHA et al, 2008).…”
Section: Introductionunclassified